Kenya County climate risk profile data - Githu, Beatrice Wanjiku; Jaquet, Stéphanie; Ghosh, Aniruddha; Maina, Wilson Nguru; Muriithi, Cyrus K; Nyakundi, Fridah Nyabate; Kinyua, Ivy Wambui; Mwongera Mugambi, Caroline Njeri (2022)
The Kenya climate risk profile data contains climate, biophysical, socio economic and demographic characteristics, crops production, stakeholders, characterization of selected value chains and risks and adaptation components. All the dataset, except climate records, were collected in three phases between 2016 and 2021. The risk profiles covered the 45 rural counties of Kenya (excluding the 2 urban counties of Nairobi and Mombasa) and were developed in partnership with the Kenya Ministry of Agriculture, Livestock, Fisheries and Cooperatives (MoALFC). Methodology: The methodology combined literature review (peer-reviewed journals, grey literature), data collection from key statistical resources (national census, county development plan, etc.), climate modelling and qualitative data collection tools such as key informant interviews, participatory workshops, and focus group discussions. For each profile, a prioritization process took place in the county with the key relevant stakeholders. The process included a presentation of the ten main value chains (VCs) of the county and a selection of the four main value chains by assessing them against a set of criteria: contribution to food security, productivity, importance to the economy; resilience to current and future climate change; population engaged in the value chain; and engagement of poor and marginalized groups.